A Study on the Effect of Intelligent Speed Adaptation (ISA) by Using Human Speech and the Acceptance - Khushairy Makhtar, Ahmad; Khameini, Ahmed; ., . (International Journal of Engineering and Technology, 2018)
Intelligent Speed Adaptation (ISA) is an in-vehicle system that support drivers compliance with the speed limit. ISA is in fact a collective term for various different systems. Today, speeding was listed as the major cause of road accidents and traffic fatalities worldwide. By having a reliable and acceptable system that could alert the drivers about the speed limit in any particular areas, it will help in reducing the number of road accidents worldwide. This study was conducted to develop a system of Intelligent Speed Adaptation (ISA) by using GPS that would alert the bus drivers in UiTM Shah Alam about speed limits in any particular areas and it must be reliable and acceptable. This research is to determine the factors of acceptance from the drivers towards the ISA system. The system developed was an advisory system. Hence, the way this system give warning about the speed limit to the driver is an important criterion to be taken care of. The output parameter of for this study is the driverâ€™s acceptance towards this ISA system and they must be happy to have this system inside their vehicles.Â Â